2002
DOI: 10.1093/hmg/11.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Temporal regulation of CFTR expression during ovine lung development: implications for CF gene therapy

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) protein is a small conductance chloride ion channel that may interact directly with other channels including the epithelial sodium channel (ENaC). CFTR is known to be more abundant in the airway epithelium during the second trimester of human development than after birth. This could be a consequence of the change in function of the respiratory epithelium from chloride secretion to sodium absorption near term. Alternatively it might reflect an addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 30 publications
7
67
0
Order By: Relevance
“…This is consistent with a growing body of evidence that CF patient lungs are abnormal at birth (Sharp, 2002;Farrell et al, 2003); that CFTR heterozygous and knockout lungs are different from homozygous normal mice (Cohen et al, 2004a); that in utero CFTR can reverse the CFTR knockout phenotype in the lungs (Fig. 9) and intestines (Larson et al, 1997); that CFTR is expressed at high levels in the developing lung (Broackes-Carter et al, 2002); and finally that transient in utero knockout of CFTR results in a CF phenotype in animals with a nor- mal CFTR genotype (Cohen and Larson, 2005).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This is consistent with a growing body of evidence that CF patient lungs are abnormal at birth (Sharp, 2002;Farrell et al, 2003); that CFTR heterozygous and knockout lungs are different from homozygous normal mice (Cohen et al, 2004a); that in utero CFTR can reverse the CFTR knockout phenotype in the lungs (Fig. 9) and intestines (Larson et al, 1997); that CFTR is expressed at high levels in the developing lung (Broackes-Carter et al, 2002); and finally that transient in utero knockout of CFTR results in a CF phenotype in animals with a nor- mal CFTR genotype (Cohen and Larson, 2005).…”
Section: Discussionsupporting
confidence: 85%
“…Additional evidence for the role of CFTR in lung organogenesis was obtained in expression studies in the fetal lung (Broackes-Carter et al, 2002). Expression of cftr-specific mRNA is approximately 75-fold greater in the fetal lung than in the adult lung (Broackes-Carter et al, 2002), and is distributed in temporal and tissuespecific patterns (Tizzano et al, 1993(Tizzano et al, , 1994Trezise et al, 1993).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Expression studies carried out in humans, mice and goats have revealed that the CFTR gene is developmentally regulated [10,[12][13][14]45]. The most well-known site of developmentally regulated CFTR expression is the airway surface epithelium, with relatively high expression during embryonic and fetal development, followed by a marked decrease in expression after birth [45].…”
Section: Discussionmentioning
confidence: 99%
“…The most well-known site of developmentally regulated CFTR expression is the airway surface epithelium, with relatively high expression during embryonic and fetal development, followed by a marked decrease in expression after birth [45]. Despite extensive studies, the mechanisms accounting for this switch in CFTR expression remain unknown.…”
Section: Discussionmentioning
confidence: 99%